PENGARUH HARGA, LOKASI DAN IKLAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN RUMAH TINGGAL DI KOTA DEPOK - Nurfitri, Ade Rachmawati; Dimyati, Dimyati (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Housing is one of the main human needs. The increase in population has caused consumer demand for housing products to also increase and is a business opportunity for housing developers. This study aims to determine the effect of price, location and social media advertising on consumer purchasing decisions. Sampling was carried out by purposive sampling method, followed by filling out a questionnaire by 100 respondents. The statistical test used SPSS version 25 with the stages of instrument testing, namely validity and reliability tests, the classic assumption test, namely the normality test, multicollinearity test and heteroscedasticity test, multiple linear regression, t test, F test and the coefficient of determination. The partial results of the study show that price has no effect on consumer purchasing decisions, while location and social media advertising have a positive and significant effect on consumer purchasing decisions. Simultaneously the price, location and social media advertising variables have a significant positive effect on consumer purchasing decisions.